A fast procedure for generating random numbers by a modification of the Marsaglia-Maclaren method - Ioannou, Ioannis Elias (Department of Computer Science, 2016)
Marsaglia and Maclaren combined two linear congruential generators in order to produce a pseudo random number sequence uniformly distributed in the range [0,2³⁵]. Their method is a considerable improvement compared with the primitive linear congruential method at the cost of greater generation time. In this thesis, a simple modification of the Marsaglia-Maclaren method is presented in which there is an alleviation of the increased generation time, and a slight further increase in randomness. The modified generator is tested extensively in a variety of statistical tests and simulation problems.